A coating structure applied to window film
By adding a silver layer with high sputtering rate on the window film, the problem of imbalance in sputtering ratio during high-power plating of silver-copper alloy film is solved, the production efficiency and thermal insulation performance are improved, and the product stability and corrosion resistance are ensured.
Patent Information
- Application Number
- CN202211474936.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-23
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-11-23
AI Technical Summary
The existing silver-copper alloy film system is prone to imbalance in silver-copper sputtering ratio during high-power plating, which affects the stability of product performance and reduces production efficiency.
During the plating production process of window film, a high sputtering silver layer is deposited by sputtering, and the thickness of the silver-copper alloy layer is reduced accordingly to improve production efficiency and enhance thermal insulation performance.
By adding silver layer, the production efficiency and thermal insulation performance of window film products are improved, the performance stability of silver-copper alloy layer is ensured, and the corrosion resistance of the product is improved.
Smart Images

Figure CN115807209B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of heat insulation technology, and in particular to a coating structure applied to a window film. Background Art
[0002] With the continuous development and maturity of magnetron sputtering coating technology, thermal insulation window film products produced and processed by magnetron sputtering film technology have been widely used in buildings and automobile window glass. In the hot summer, the thermal insulation window film effectively blocks the transmission of solar radiation energy into the room (car), thereby reducing people's energy consumption for indoor (car) cooling, achieving the purpose of energy saving and consumption reduction and meeting people's life needs.
[0003] Precious metal silver is a material with excellent performance commonly used in the plating of window film products. Silver film has the characteristics of high light transmittance and high heat insulation. However, pure metal silver film is easy to oxidize and sulfide, so it is necessary to add a stable metal material or metal compound material as a protective film layer on the silver film to protect it. If a plated compound is used as a protective film on the silver film, a reactive sputtering process is required. The reactive sputtering process is complex to control, the production efficiency is low, and the production cost of the product is high. In addition, a metal film can also be used as a protective film, but the light transmittance and heat insulation performance of the entire film layer will be affected if the metal film is plated too thick, and the protective effect will be poor if the plating is too thin. Therefore, silver alloy materials (such as AgCu) are usually used to plate thermal insulation film products, but this silver-copper alloy film layer is prone to an imbalance in the silver-copper sputtering ratio during high-power plating, thereby affecting the function of the deposited layer on the substrate and causing unstable product performance. Therefore, a normal proportion of silver-copper alloy deposits can only be stably plated at a relatively low power, which has a great impact on the efficient production of the product. Summary of the invention
[0004] The purpose of the present invention is to provide a coating film system design for high-performance heat-insulating film applied to window glass, which solves the problem that the original silver-copper alloy film system products are prone to silver-copper sputtering ratio imbalance (affecting the function of the deposited layer on the substrate) when the silver-copper alloy film layer is plated with high power, and also improves the problem of low production efficiency caused by using reduced power plating products. In the plating production process of the window film product, the present invention deposits a silver layer with a higher sputtering rate by sputtering, and correspondingly reduces the thickness of the silver-copper alloy layer with a lower sputtering rate to achieve the purpose of improving production efficiency, and at the same time, the heat insulation performance of the window film product can be enhanced.
[0005] The present invention provides a coating structure applied to a window film, comprising a substrate layer, on which a first nickel-chromium alloy layer, a first silver-copper alloy layer, a silver layer, a second silver-copper alloy layer and a second nickel-chromium alloy layer are sequentially deposited.
[0006] By adopting the above technical scheme, the optimized and improved film system adds a precious metal silver layer on the basis of the original silver-copper alloy film system. Since pure silver has a high sputtering deposition rate and excellent optical properties, it can improve the production efficiency of window film products and enhance the infrared blocking effect of window film products. At the same time, the thickness of the silver-copper alloy layer in the window film coating is reduced accordingly, and it is easier to obtain a silver-copper alloy layer with stable performance during processing, and the process performance is also improved. The structure and composition of the optimized coating are reasonable, and both the nickel-chromium alloy and the silver-copper alloy layers can play a good protective role on the silver layer. Therefore, the plated window film products have good corrosion resistance, which can make the product performance stable and long-lasting. In summary, the improved coating film system effectively improves the shortcomings of low product production efficiency, poor processing technology, and unstable product performance caused by the original film system, improves the production efficiency of window film products, and also enhances the thermal insulation performance of the product.
[0007] As a possible preferred embodiment, the purity of silver in the silver layer is greater than 99.9 wt %.
[0008] As a possible preferred embodiment, the silver content in the first silver-copper alloy layer and the second silver-copper alloy layer are both 45wt% to 97wt%, and the copper content is both 3wt% to 55wt%.
[0009] As a possible preferred embodiment, a first nickel-chromium alloy layer is deposited between the first silver-copper alloy layer and the substrate layer; a second nickel-chromium alloy layer is deposited on the second silver-copper alloy layer, and the second nickel-chromium alloy layer is in contact with the medium, further improving the corrosion resistance of the thermal insulation film product.
[0010] As a possible preferred embodiment, the nickel content in the first nickel-chromium alloy layer and the second nickel-chromium alloy layer are both 25wt% to 83wt%, and the chromium content in the first nickel-chromium alloy layer and the second nickel-chromium alloy layer are both 17wt% to 75wt%.
[0011] As a possible preferred manner, the deposition is achieved by using a magnetron sputtering method.
[0012] As a possible preferred embodiment, the material of the substrate layer is polyethylene terephthalate. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation on the present invention. The drawings of the present invention are only used to illustrate the structures shown and do not limit the size, thickness or relative size of the components in the structures. In the drawings:
[0014] Figure 1 A schematic diagram of the window film coating structure disclosed in an embodiment of the present invention;
[0015] Figure 2 This is the spectrum curve obtained for the window film product of Test Example 1.
[0016] Among them: 1-substrate layer; 2-first nickel-chromium alloy layer; 3-first silver-copper alloy layer; 4-silver layer; 5-second silver-copper alloy layer; 6-second nickel-chromium alloy layer. DETAILED DESCRIPTION
[0017] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0018] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0019] The inventor of the present invention has found that when the silver-copper alloy film system of the existing window film is deposited by magnetron sputtering, the silver-copper sputtering ratio will be unbalanced when the sputtering power is large, thereby affecting the function of the deposited layer on the substrate and causing the product to have unstable performance; therefore, only a lower sputtering power can be used to plate the product, but the lower sputtering power will reduce the production efficiency of the product. In view of the above problems, the coating film system of the original window film is optimized to improve its processability and enhance the performance of the product.
[0020] The inventor of the present invention adds a metallic silver coating to the coating film system of the original window film, which can not only improve the production efficiency of such window film products, but also enhance the heat insulation performance of the window film products.
[0021] like Figure 1 As shown, the present invention discloses a coating structure applied to a window film, comprising a substrate layer 1, on which a first nickel-chromium alloy layer 2, a first silver-copper alloy layer 3, a silver layer 4, a second silver-copper alloy layer 5 and a second nickel-chromium alloy layer 6 are sequentially deposited.
[0022] In the present invention, the substrate layer 1 should have good light transmittance and low haze. The substrate layer 1 is generally made of an optical-grade film, such as polyethylene terephthalate film, abbreviated as PET in English.
[0023] In the present invention, by adding a layer of silver layer 4, the thickness of the plated first silver-copper alloy layer 3 and the second silver-copper alloy layer 5 is correspondingly reduced, and a silver-copper alloy layer with stable performance can be sputtered and deposited using appropriate (medium or low) power. At the same time, due to the high sputtering rate of the added silver, the production efficiency of the plated window film product is correspondingly improved. The purity of the silver target used for the silver layer 4 is generally required to be greater than 99.9wt%.
[0024] In the present invention, a first nickel-chromium alloy layer 2 is deposited between the first silver-copper alloy layer 3 and the substrate layer 1; and a second nickel-chromium alloy layer 6 is deposited on the second silver-copper alloy layer 5, and the second nickel-chromium alloy layer 6 is in contact with the medium.
[0025] The first nickel-chromium alloy layer 2 and the second nickel-chromium alloy layer 6 respectively function as a transition layer and a protective layer, so as to achieve better bonding between the substrate and the film layer and enhance the anti-oxidation and corrosion resistance of the coating layer.
[0026] As used herein, the "medium" refers to the environment in which the silver layer protective film is used, such as water, oil, solution, and air. In the present invention, the medium is air.
[0027] Generally, the composition of the nickel-chromium alloy layer is (Ni 25wt%~83wt%, Cr12wt%~75wt%), the composition of the silver-copper alloy layer is (Ag 45wt%~97wt%, Cu3wt%~55wt%), and the composition of the silver layer is (Ag 99.9wt%).
[0028] In the present invention, the thicknesses of the nickel-chromium alloy layer, the silver-copper alloy layer and the silver layer can be optimized and designed accordingly according to the optical properties and thermal properties required by the window film product.
[0029] It should be noted that the present invention does not impose any specific restrictions on the specific thickness of each coating layer. The thickness of the coating layer can be adjusted arbitrarily based on the requirements of the window film product on optical properties and thermal properties. Therefore, the present invention does not impose any upper or lower limit on the thickness of the coating layer.
[0030] In order to achieve good deposition effect of each layer, in the present invention, each layer can be deposited by magnetron sputtering. When magnetron sputtering each layer, each process parameter can be selected according to the process parameters of the layer to be deposited. Since each process parameter is existing, it will not be described in detail.
[0031] Example
[0032] Example 1
[0033] This embodiment discloses a coating structure applied to a window film product: PET layer (thickness 23 μm) / nickel-chromium alloy layer (thickness 1.0 nm) / silver-copper alloy layer (thickness 2.0 nm) / silver layer (thickness 3.0 m) / silver-copper alloy layer (thickness 2.0 nm) / nickel-chromium alloy layer (thickness 1.0 nm).
[0034] The present embodiment also discloses a method for preparing the coating applied to the window film product, comprising: depositing a 1.0 nm nickel-chromium alloy layer, a 2.0 nm silver-copper alloy layer, a 3.0 nm silver layer, a 2.0 nm silver-copper alloy layer and a 1.0 nm nickel-chromium alloy layer on the PET layer in sequence by a magnetron sputtering method, wherein the sputtering targets are: a nickel-chromium alloy target (nickel content is 80 wt %, chromium content is 20 wt %); a silver-copper alloy target (silver content is 92 wt %, copper content is 8 wt %); a silver target (silver content is 99 wt %).
[0035] The coating speed of the window film coating was statistically analyzed and the results are shown in Table 1.
[0036] According to the method specified in GB2680 standard, the prepared window film product was subjected to spectral (wavelength 280nm ~ 2500nm) transmission test using Japan Shimadzu-UV3600 spectrophotometer, and the obtained visible light transmittance and shading coefficient results are shown in Table 1.
[0037] Example 2
[0038] This embodiment discloses a coating structure applied to a window film product: PET layer (thickness 23 μm) / nickel-chromium alloy layer (thickness 1.5 nm) / silver-copper alloy layer (thickness 2.0 nm) / silver layer (thickness 4.5 nm) / silver-copper alloy layer (thickness 2.0 nm) / nickel-chromium alloy layer (thickness 1.5 nm).
[0039] The present embodiment also discloses the preparation method for the above-mentioned window film product, comprising: depositing a 1.5 nm nickel-chromium alloy layer, a 2.0 nm silver-copper alloy layer, a 4.5 nm silver layer, a 2.0 nm silver-copper alloy layer and a 1.5 nm nickel-chromium alloy layer on the PET layer in sequence by a magnetron sputtering method, wherein the sputtering targets are: a nickel-chromium alloy target (nickel content is 80 wt %, chromium content is 20 wt %); a silver-copper alloy target (silver content is 92 wt %, copper content is 8 wt %); a silver target (silver content is 99 wt %).
[0040] The coating speed of the window film coating was statistically analyzed and the results are shown in Table 1.
[0041] According to the method specified in GB2680 standard, the prepared window film product was subjected to spectral (wavelength 280nm ~ 2500nm) transmission test using Japan Shimadzu-UV3600 spectrophotometer, and the obtained visible light transmittance and shading coefficient results are shown in Table 1.
[0042] Example 3
[0043] This embodiment discloses a coating structure applied to a window film product: PET layer (thickness 36 μm) / nickel-chromium alloy layer (thickness 2.0 nm) / silver-copper alloy layer (thickness 2.0 nm) / silver layer (thickness 7.0 nm) / silver-copper alloy layer (thickness 2.0 nm) / nickel-chromium alloy layer (thickness 2.0 nm).
[0044] The present embodiment also discloses the preparation method for the window film product, comprising: depositing a 2.0 nm nickel-chromium alloy layer, a 2.0 nm silver-copper alloy layer, a 7.0 nm silver layer, a 2.0 nm silver-copper alloy layer and a 2.0 nm nickel-chromium alloy layer on the PET layer in sequence by a magnetron sputtering method, wherein the sputtering targets are: a nickel-chromium alloy target (nickel content is 80 wt %, chromium content is 20 wt %); a silver-copper alloy target (silver content is 92 wt %, copper content is 8 wt %); a silver target (silver content is 99 wt %).
[0045] The coating speed of the window film coating was statistically analyzed and the results are shown in Table 1.
[0046] According to the method specified in GB2680 standard, the prepared window film product was subjected to spectral (wavelength 280nm ~ 2500nm) transmission test using Japan Shimadzu-UV3600 spectrophotometer, and the obtained visible light transmittance and shading coefficient results are shown in Table 1.
[0047] Example 4
[0048] This embodiment discloses a coating structure applied to a window film product: PET layer (thickness 50 μm) / nickel-chromium alloy layer (thickness 2.0 nm) / silver-copper alloy layer (thickness 3.0 nm) / silver layer (thickness 9.6 nm) / silver-copper alloy layer (thickness 3.0 nm) / nickel-chromium alloy layer (thickness 2.0 nm).
[0049] The present embodiment also discloses the preparation method for the above-mentioned window film product, comprising: depositing a 2.0nm nickel-chromium alloy layer, a 3.0nm silver-copper alloy layer, a 9.6nm silver layer, a 3.0nm silver-copper alloy layer and a 2.0nm nickel-chromium alloy layer on the PET layer in sequence by a magnetron sputtering method, wherein the sputtering targets are: a nickel-chromium alloy target (nickel content is 80wt%, chromium content is 20wt%); a silver-copper alloy target (silver content is 92wt%, copper content is 8wt%); a silver target (silver content is 99wt%).
[0050] The coating speed of the window film coating was statistically analyzed and the results are shown in Table 1.
[0051] According to the method specified in GB2680 standard, the prepared window film product was subjected to spectral (wavelength 280nm ~ 2500nm) transmission test using Japan Shimadzu-UV3600 spectrophotometer, and the obtained visible light transmittance and shading coefficient results are shown in Table 1.
[0052] Comparative Example 1
[0053] This comparative example discloses a coating structure applied to a window film product: PET layer (thickness 23 μm) / nickel-chromium alloy layer (thickness 1.0 nm) / silver-copper alloy layer (thickness 5.0 nm) / nickel-chromium alloy layer (thickness 1.0 nm). The sputtering targets are: nickel-chromium alloy target (nickel content is 80 wt%, chromium content is 20 wt%); silver-copper alloy target (silver content is 92 wt%, copper content is 8 wt%).
[0054] This comparative example also discloses the preparation method for the window film coating, comprising: depositing a 1.0 nm nickel-chromium alloy layer, a 5.0 nm silver-copper alloy layer and a 1.0 nm nickel-chromium alloy layer on the PET layer in sequence by a magnetron sputtering method, and calculating the plating speed of the thermal insulation film coating. The results are shown in Table 1.
[0055] According to the method specified in GB2680 standard, the prepared window film product was subjected to spectral (wavelength 280nm ~ 2500nm) transmission test using Japan Shimadzu-UV3600 spectrophotometer, and the obtained visible light transmittance and shading coefficient results are shown in Table 1.
[0056] Comparative Example 2
[0057] This comparative example discloses a coating structure applied to a window film product: PET layer (thickness 23 μm) / nickel-chromium alloy layer (thickness 1.0 nm) / silver-copper alloy layer (thickness 12.3 nm) / nickel-chromium alloy layer (thickness 1.0 nm). The sputtering targets are: nickel-chromium alloy target (nickel content is 80 wt%, chromium content is 20 wt%); silver-copper alloy target (silver content is 92 wt%, copper content is 8 wt%).
[0058] This comparative example also discloses the preparation method for the window film coating, comprising: depositing a 1.0 nm nickel-chromium alloy layer, a 12.3 nm silver-copper alloy layer, and a 1.0 nm nickel-chromium alloy layer on the PET layer in sequence by a magnetron sputtering method, and calculating the plating speed of the thermal insulation film coating. The results are shown in Table 1.
[0059] According to the method specified in GB2680 standard, the prepared window film product was subjected to spectral (wavelength 280nm ~ 2500nm) transmission test using Japan Shimadzu-UV3600 spectrophotometer, and the obtained visible light transmittance and shading coefficient results are shown in Table 1.
[0060] Table 1
[0061]
[0062] As shown in Table 1, the present invention can significantly increase the coating speed of window film products by adding a layer of precious metal silver on the basis of the original silver-copper film system. The increase in coating speed is basically more than 15%, thereby improving production efficiency. At the same time, the shading coefficient of the window film is also reduced, and the thermal insulation performance of the window film product is improved.
[0063] The spectrum curve of the window film product prepared in Example 1 is tested by a spectrophotometer. Figure 2 shown.
[0064] Depend on Figure 2 From the spectrum curve of the window film product, we can see that this type of window film has a higher visible light transmittance and better infrared blocking rate, so it is worth promoting and using.
[0065] In summary, the optimized and improved window film coating is to add a precious metal silver layer on the basis of the original silver-copper alloy film system. Due to the high sputtering deposition rate of pure silver and its excellent spectral characteristics, it can improve the production efficiency of window film products and enhance the infrared blocking effect of window film products. At the same time, the thickness of the silver-copper alloy layer in the window film coating is correspondingly thinned, and it is easier to obtain a silver-copper alloy layer with stable performance during processing, and the process performance is also improved. The structure and composition of the optimized coating are reasonable, and both the nickel-chromium alloy and the silver-copper alloy layers can play a good protective role on the silver layer, so the plated window film products have good corrosion resistance, and the product usability can also be stable and long-lasting. In summary, the improved coating film system effectively improves the shortcomings of the original film system products, such as low production efficiency, poor processing technology, and unstable product performance, so that the production efficiency of the window film is improved, and the thermal insulation performance of the window film products is also enhanced.
[0066] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A coating structure applied to a window film, characterized in that: It comprises a substrate layer, on which a first nickel-chromium alloy layer, a first silver-copper alloy layer, a silver layer, a second silver-copper alloy layer and a second nickel-chromium alloy layer are sequentially deposited; The substrate layer is a polyethylene terephthalate film; The thickness of the substrate layer is 23 μm, the thickness of the first nickel-chromium alloy layer and the second nickel-chromium alloy layer are both 1 nm or 1.5 nm, and the thickness of the silver layer is 3 nm or 4.5 nm.
2. The coating structure according to claim 1, characterized in that: The purity of silver in the silver layer is greater than 99.9wt%.
3. The coating structure according to claim 1, characterized in that: The silver content in the first silver-copper alloy layer and the second silver-copper alloy layer is 45wt% to 97wt%, and the copper content is 3wt% to 55wt%.
4. The coating structure according to claim 1, characterized in that: The nickel content in the first nickel-chromium alloy layer and the second nickel-chromium alloy layer are both 25wt% to 83wt%, and the chromium content in the first nickel-chromium alloy layer and the second nickel-chromium alloy layer are both 17wt% to 75wt%.
5. The coating structure according to claim 1, characterized in that: A first nickel-chromium alloy layer is deposited between the first silver-copper alloy layer and the substrate layer; a second nickel-chromium alloy layer is deposited on the second silver-copper alloy layer, and the second nickel-chromium alloy layer is in contact with the medium.
6. The coating structure according to claim 1 or 5, characterized in that: The deposition is achieved by magnetron sputtering.
Citation Information
Patent Citations
Low-radiation glass
CN113149461A
KR20200089113A